Technology integration through acceptance of e-learning among preservice teachers - Ika Ratih Sulistiani; Punaji Setyosari; Cholis Sa'dijah; Henry Praherdhiono (Institute of Advanced Engineering and Science, 2023)
The rapid evolution of online learning necessitates the agility of future educators. Future teachers’ technological attitudes and abilities will be affected by the explication of the role of technology in learning in teacher education. Therefore, preservice teachers must be prepared to implement technology in their future classrooms. This study investigated the effect of technological pedagogical content knowledge (TPACK) competency on the technology acceptance model (TAM)-measured intention to use from two perspectives: self-confidence and self-regulation. Thus, six hypotheses are proposed to investigate the relationship between TPACK proficiency and the intent to use technology. The population of 224 preservice teachers at one Indonesian tertiary institution was analyzed using structural equation modeling (SEM) to confirm five of the six hypotheses. It is stated that attitudes toward TPACK competence positively correlate with self-regulation, self-efficacy, and intent to use technology. In addition, the derived model can account for approximately 53.8% of the intention to integrate technology in the classrooms of preservice teachers.